Detailed Transabdominal Fetal Anatomic Scanning in the Late First Trimester Versus the Early Second Trimester of Pregnancy. (1st January 2015) - Yagel, Simcha; Cohen, Sarah M.; Porat, Shay; Daum, Hagit; Lipschuetz, Michal; Amsalem, Hagai; Messing, Baruch; Valsky, Dan V.
Abstract : Objectives: To compare visualization rates for early targeted organ scanning at gestational ages ranging from 11 weeks 3 days to 13 weeks 2 days versus 14 weeks 3 days to 16 weeks 2 days. Methods: We conducted a prospective longitudinal study of patients who presented for nuchal translucency (NT) screening and targeted organ scanning. Extended targeted organ scanning, including the central nervous system, face and neck, chest, heart (including complete echocardiography), digestive system, abdominal wall, urinary system, skeleton, and umbilical cord with its insertion and placenta, was performed on gravidas in 2 age ranges. Uterine artery Doppler mapping was performed during the second scan. All cases were examined twice: once at NT screening (up to 13 weeks 2 days) and again in the early second trimester. Results: A total of 408 women were recruited and scanned twice. Three abnormalities were diagnosed in the second scan that were not seen in the first: dysplastic long bones, tricuspid stenosis, and cleft lip (without palate involvement). None had chromosomal anomalies. Successful visualization rates in all organ systems exceeded 94% in the second trimester. At the first‐trimester scan, some systems had high success rates, whereas others were very low; eg, in the brain, the cerebellum and posterior fossa were visualized successfully approximately 50% of the time and the upper lip only approximately 10%. On fetal echocardiography, the 4‐chamber view and outflow tracts were imaged successfully approximately 40% of the time, and the kidneys approximately 35%. Uterine artery Doppler mapping was possible in all patients on at least one side. On third‐trimester follow‐up, we diagnosed 1 mild pulmonary stenosis, 1 autosomal recessive polycystic kidney disease, and 1 ventricular septal defect. Conclusions: The early second‐trimester scan was much more productive than targeted organ scanning performed during the NT window. When counseling women regarding the optimal time for early transabdominal targeted organ scanning, successful visualization rates for various organ systems should be considered.